Evaluation of Cytotoxic Activity Alkaloid Fractions of Zanthoxylum acanthopodium DC. Fruits - Syari, Dina Maya; Rosidah, Rosidah; Hasibuan, Poppy Anjelisa Zaitun; Haro, Ginda; Satria, Denny (Open Access Macedonian Journal of Medical Sciences, 2019)
AIM: This study was carried out to investigate cytotoxic activity towards T47D, 4T1, MCF-7, HeLa, and Raji cells of alkaloid fractions of Zanthoxylum acanthopodium DC. fruits. Zanthoxylum acanthopodium DC. METHODS: The fruit was extracted by maceration. The ethanol extract was fractionated with liquid-liquid extraction using n-hexane, chloroform at pH 3,7, and 9 to obtained alkaloid fractions. Cytotoxic activity for fraction chloroform at pH 7 and 9 was determined with MTT assay. RESULTS: The IC50 of fraction chloroform at pH 7 and 9 was (92.67 ± 1.37; 71.87 ± 1.04; 159.87 ± 0.63; 123.39 ± 0.81; and 103.09 ± 0.58 µg/mLfor pH 7) and (451.29 ± 25.48; 247.18 ± 2.82; 318.46 ± 5.40; 303.96 ± 8.75; and 181.45 ± 1.35 µg/mL for pH 9) respectively. CONCLUSION: The results reveal that alkaloid fractions at pH 7 and 9 of Zanthoxylum acanthopodium DC. Fruits have cytotoxic activity. Our further study is to isolate and assesses anticancer activity from alkaloid compounds.